Last Project Standing : Civics and Sympathy in Post-Welfare Chicago - Fennell, Catherine, 1976- (Book collections on Project MUSE., 2015)
This study of Chicago's urban planning over the past two decades has three aims. The first is to understand how and with what effect a built environment in flux became central within the arguments that public housing residents advanced concerning their protection at a post-welfare moment. The book's second aim is to examine how feelings of interpersonal and collective obligation emerged, expanded, and were cut short in the wake of public housing. Finally, this study aims to understand the terms on which residents of Chicago's public housing might be included within a city that has, over the past two decades, seen the demolition of residents' homes and a marked decline in the city's African American population.